Sternal fixation techniques following sternotomy for preventing sternal wound complications - Pinotti, Karin F. [UNESP]; El Dib, Regina [UNESP]; Cataneo, Daniele C. [UNESP]; Rodrigues, Olavo Ribeiro; Silva, Leandro Re; Cataneo, Antonio José Maria [UNESP] (Wiley, 2014)
This is the protocol for a review and there is no abstract. The objectives are as follows: To evaluate the efficacy and safety of sternal fixation techniques for preventing sternal wound complications following sternotomy .